Tracheostomy: Complications and Causes of Complications - Alijanpour, Ebrahim (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Tracheostomy is one of the critical surgical procedures in the case of airway obstruction and in patients with long-term intubation; on the other hand, it has complications, that some of which are common. Objectives: The aim of this study was to determine the complications and their underlying causes in patients admitted to the intensive care unit (ICU). Methods: This descriptive, analytical study was performed on 107 patients eligible to participate in the research in ICU wards of Babol hospitals, in northern Iran, in 1394. Patients were evaluated for 16 common Tracheostomy complications immediately after tracheostomy, up to 1 month after removal of the tracheal tube, using the checklist for 4 months. The underlying causes of complications were determined by assessed the causes of admission, the method of tracheostomy, the history of diseases affecting complications and the quality of nursing care from tracheostomy through a standard care checklist. Results: The highest percentage of units (21.5%) was experienced one complication, 19.6% units were two complications, and 5.6% had no complication and 0.9% of the units showed most complications (11). The most common complications were infections and redness (46.7%(, swelling (43.9%), and bleeding and air leakage from tracheostomy (33.6%), respectively. Patients with diabetes and high blood pressure, patients with a surgical tracheostomy, and patients with ischemic heart disease, experienced the most complications, respectively. The quality of nursing care was determined 66.4% in average grade. Conclusions: Tracheostomy is a way to continue the patient’s respiration, in spite of inevitable complications. The method of stoma formation, underlying diseases and the quality of nursing care has a direct relationship with its complications. It is suggested that nurses improve the quality of nursing care to reduce the complications.